Public space and art − The places of the polis - Oláh Mátyás, László (Studia Mundi – Economica, 2015)
In my essay Public Space and Art − The Places of the Polis I’m studying the questions of contemporary public art and sculpture. On analysing the concept of the personal remembrance, the collective and the historical memory, the viewpoints of the Urban Development, and the characteristic public statues of the last 25 years in Central Europe, I have been researching the answer to the question how had the special requirements of the public art been changing.